(untitled) (Research, Society and Development, 2024)
The objective of this article is to evaluate the effectiveness of an awareness campaign in reducing food waste in a Food and Nutrition Unit (UAN) in the municipality of Alfenas, in the south of Minas Gerais, Brazil. The per capita waste percentage was investigated before and after the campaign’s implementation at the UAN. Initially, food waste was significant, with high levels of plate and tray waste, especially on days with less accepted menus. After the campaign, there was a notable reduction in waste, highlighting the positive impact of educational initiatives on consumer behavior change. The results indicate that menu adjustments and strict portion control are essential to minimize waste. It is concluded that educational campaigns and efficient management are crucial for long-term reduction of food waste in UANs, promoting sustainable eating practices and greater responsibility in consumption.